Genus-level revision of the Heterozerconoidea (Parasitiformes: Mesostigmata) - Klompen, Hans; Gerdeman, Beverly S. (Zootaxa, 2023)
The genera of Heterozerconoidea are revised based on a species-level analysis of relationships in the group. The family Discozerconidae in its current state may be paraphyletic. Diagnoses for the genera are updated, and a catalog of all described species is provided. As part of this re-analysis two new genera, Amyzozercon and Ecuazercon, and four new species are described, and a key to the genera is provided. Possible evolutionary implications of the proposed set of relationships in terms of biogeography and the evolution of podospermy are discussed.